The Institutionalization of Islam in the Ottoman Empire: An Integrated Perspective - Semi Priyatno; Irfan Musonif; Kholid Mawardi (PT.Hassan Group Publisher, 2026)
Studies on Islam in the Ottoman Empire have primarily examined religious authority, governance, and social institutions as separate domains, leaving limited understanding of how these elements functioned as an integrated institutional framework. This study aims to analyze the institutionalization of Islam in the Ottoman Empire by examining the relationship between religious authority, governance, and social order. The research employed a qualitative library-based approach using documentary and thematic analysis. Data were derived from twenty peer-reviewed scholarly publications (2020–2025) and eight foundational works on Ottoman and Islamic history. The findings indicate that the institutionalization of Islam was shaped through three interconnected dimensions. First, religious authority was institutionalized through the integration of the ulama, educational institutions, judicial structures, and the office of the Shaykh al-Islam into imperial administration. Second, governance was not merely legitimized by Islam but was partially structured through Islamic legal and administrative institutions. Third, social order was sustained through networks of waqf, educational systems, and communal arrangements that regulated social relations and welfare. These dimensions collectively formed an integrated institutional ecosystem that strengthened political legitimacy, administrative coherence, and social stability. The study contributes to Ottoman and Islamic studies by demonstrating that Islam functioned not only as a religious tradition but also as a comprehensive institutional framework shaping governance and social organization.